1995
DOI: 10.1097/00005392-199508000-00065
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Surgery in the Management of Pediatric Pelvic Rhabdomyosarcoma

Abstract: Exenterative surgery is frequently required to achieve a durable complete response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Although vaginal RMS is rare, it is the most common neoplasm of the vagina in young females with a median age of two . Historically, radical surgical approaches such as total/partial vaginectomy, hysterectomy, and pelvic exenteration have resulted in high treatment morbidity and significant side effects with poor outcomes . Conservative treatment is the accepted management of vaginal RMS resulting in excellent outcome with an overall survival rate of more than 80% at 10 years .…”
Section: Discussionmentioning
confidence: 99%
“…Although vaginal RMS is rare, it is the most common neoplasm of the vagina in young females with a median age of two . Historically, radical surgical approaches such as total/partial vaginectomy, hysterectomy, and pelvic exenteration have resulted in high treatment morbidity and significant side effects with poor outcomes . Conservative treatment is the accepted management of vaginal RMS resulting in excellent outcome with an overall survival rate of more than 80% at 10 years .…”
Section: Discussionmentioning
confidence: 99%
“…Variations include anterior pelvic exenteration, which spares the rectosigmoid, and posterior pelvic exen-teration, which spares the bladder [19]. Pelvic exenteration has also been described in the management of other pelvic tumors such as bladder cancer and pelvic sarcomas [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these methods were successful in bladder salvage [2–4], but bladder function after treatment, especially with radiotherapy, is either not stated [2,3] or reported to be poor in most cases [4,6]. Others found that total cystectomy was usually indicated and primary chemo‐therapy/radiotherapy was not enough to replace radical surgery [5,7,8]. Furthermore, some authors argued that given current innovative methods of continent urinary diversion, radical cystectomy is not considered mutilating [9].…”
Section: Introductionmentioning
confidence: 99%